Crevice corrosion of biomedical alloys: A novel method of assessing the effects of bone cement and its chemistry12. Issue 5 (29th January 2013) - Bryant, Michael; Hu, Xinming; Farrar, Richard; Brummitt, Ken; Freeman, Robert; Neville, Anne
Abstract: In this study, five commercially available poly(methyl methacrylate) PMMA bone cements were tested to investigate the effects of antibiotics on the severity of crevice corrosion. Bone cements with varying chemistry were also tested. A test method was developed in part reference to ASTM F746‐04. Cylindrical specimens were fitted with a bone cement tapered collar, creating consistent crevice conditions. Crevice corrosion was then studied using potentiodynamic polarization techniques in 0.9% NaCl solution (pH7.4) at 37°C. Surface analyses using a light microscope and scanning electron microscopy were also conducted to investigate the surface morphology after accelerated electrochemical testing. Initial testing of commercially available bone cements indicated that different PMMA bone cements can affect the initiation and propagation mechanism of crevice corrosion. Further studies, utilising electrochemical and mass spectroscopy techniques, have identified that the addition of radiopaque agent and antibiotics affect the initiation mechanisms of 316L stainless steel, whilst significantly increasing the extent of propagation in CoCrMo alloys. © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 2013.